SILVER NANOPARTICLES FROM TRIANTHEMA PORTULACASTRUM: GREEN SYNTHESIS, CHARACTERIZATION, ANTIBACTERIAL AND ANTICANCER PROPERTIES - K, Gowri Shankar; Pradhan, Namrata; K, Masilamani; Fleming, Albin T (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: In this study, silver nanoparticles (SNPs) were synthesized using an aqueous extract of Trainthema portulacastrum and silver ions (Ag+) which have been proven against certain pathogenic bacterial strains and hepatocellular carcinoma (HepG2) cell line. Methods: The bio fabricated nanoparticles were confirmed by surface plasmon resonance which were characterized by biophysical measures utilizing the ultraviolet-visible spectroscopy, scanning electron microscopy (SEM), energy dispersive X-ray, and transmission electron microscope (TEM), Fourier transform infrared spectroscopy, particle size analyzer, and X-ray diffraction. Antibacterial efficacy against Enterobacter aerogens, Proteus mirabilis, Escherichia coli, Staphylococcus epidermis, and Bacillus subtilis. The effect of SNPs tested against HepG2 and NIH/3T3 cell line exhibits a dose-dependent toxicity. Results and Conclusion: The SEM and TEM images confirmed the presence of spherical and hexagonal shape (0.3-4 Î¼m) of nanocrystalline particles with the size range of 11.5-29.2 nm. The average particles size of SNPs is 190.3Â±17.0 nm. Antibacterial activity was carried out by agar well diffusion method against different pathogenic bacteria of which B. subtilis showed a significant zone of inhibition 8.66 mm and 12.0 mm for aqueous plant extract and synthesized SNPs. The effect of SNPs tested against HepG2 and NIH/3T3 cell line exhibits a dose-dependent toxicity. In case of HepG2, the cell viability was decreased to 50% (IC50) at the concentration of 173.8Â±0.84 Î¼g/mL. From the results, it can be concluded that the SNPs fabricated using green synthesis method will be a promising candidate in the biomedical field, due to its high bioactive properties. Keywords: Silver nanoparticles, Trainthema portulacastrum, Antibacterial activity, Cytotoxic activity.